Performance Analysis of Signalized Intersections on Jalan Trunojoyo - Jalan Teja Pamekasan Using The 2014 PKJI Method - Fairus Zabadi Fairus; Wahyu Yuwana (Journal of Civil Engineering and Planning (JCEP), 2023)
Pamekasan is one of the districts currently developing on Madura Island. This is characterized by a strategic location and also being the center of the crowd. The aim of this research is to determine the performance of signalized intersections on Jalan Trunojoyo - Jalan Teja Pamekasan as well as alternatives for dealing with problems at these intersections using the PKJI 2014 method. This method is used to determine the performance of signalized intersections, namely capacity, queue length, delays and degree of saturation. From the results of the analysis and calculation of the capacity value on Jalan Trunojoyo it is 1789.18 cur/hour while on Jalan Teja it is 227.31 cur/hour, from the results of the analysis and calculation the value of the queue length on Jalan Trunojoyo is 4.9m while on Jalan Teja it is 3.4m. The results of the analysis and calculation of the delay value on Jalan Trunojoyo are 2.72 seconds/cur while on Jalan Teja it is 24.2 seconds/cur, from the results of the analysis and calculation of the value of the degree of saturation on Jalan Trunojoyo it is 0.36 while on Jalan Teja it is 0.36. The alternative is to change the two phases of the road from the south of Trunojoyo and from the west of Teja during peak hours so as to reduce congestion and delays that occur on the road.